Comparison of plastic stent versus metal stent in preoperative biliary drainage for pancreatic head cancer with neoadjuvant chemoradiotherapy. (12th March 2021) - Kobayashi, Kiyoyuki; Kobara, Hideki; Kamada, Hideki; Kohno, Toshiaki; Namima, Daisuke; Fujita, Naoki; Yamana, Hiroki; Fujihara, Shintaro; Okano, Keiichi; Masaki, Tsutomu
Abstract: Background: While neoadjuvant chemotherapy and chemoradiotherapy (NACRT) for pancreatic head cancer are effective, preoperative endoscopic biliary drainage (EBD) is necessary for managing obstructive jaundice and cholangitis during the preoperative waiting period. Nevertheless, ideal choice of stent type is unclear. We compared plastic stents (PS) and metal stents (MS) in these situations. Methods: We retrospectively studied 43 patients who successfully underwent preoperative EBD prior to NACRT for pancreatic head cancer at a single institution. We divided patients into PS (n = 22) and MS (n = 21) groups. The primary outcome was the rate of re‐interventional drainage rate before surgery. Secondary outcomes were rates of EBD‐associated and postoperative complications and total costs in the pre‐ and perioperative periods. Results: The re‐intervention rate was significantly greater in the PS group than in the MS group (95% vs 4.8%, respectively, P < 0.05). EBD‐associated and postoperative complications were significantly less common in the MS group ( P < 0.05). The average total preoperative medical costs were significantly lower in the MS group (PS vs MS: 528, 597 vs 395, 891 JPY, P = 0.004). Conclusions: MS can be the first choice for EBD in patients undergoing NACRT for pancreatic head cancer. MS may be less costly overall. Abstract : Highlight Retrospectively comparing the efficacy and cost‐benefit of plastic stents versus metal stents in preoperative endoscopic biliary drainage for pancreatic head cancer with neoadjuvant chemoradiotherapy, Kobayashi and colleagues concluded that metal stents can be the first choice. Metal stents were also found to be more cost‐beneficial in the preoperative period.